Determination of selected synthetic cannabinoids and their metabolites by micellar electrokinetic chromatography--mass spectrometry employing perfluoroheptanoic acid-based micellar phase - Švidrnoch, Martin; Přibylka, Adam; Maier, Vítězslav (Talanta, 2016)
Perfluoroheptanoic acid was employed as a volatile micellar phase in background electrolyte for micellar electrokinetic chromatography-tandem mass spectrometry separation and determination of 15 selected naphthoyl- and phenylacetylindole- synthetic cannabinoids and main metabolites derived from JWH-018, JWH-019, JWH-073, JWH-200 and JWH-250. The influence of concentration of perfluoroheptanoic acid in background electrolytes on the separation was studied as well as the influence of perfluoroheptanoic acid on mass spectrometry detection. The background electrolyte consisted of 75 mM perfluoroheptanoic acid, 150 mM ammonium hydroxide pH 9.2 with 10% (v/v) propane-2-ol allowed micellar electrokinetic chromatography separation together with mass spectrometry identification of the studied parent synthetic cannabinoids and their metabolites. The limits of detection of studied synthetic cannabinoids and metabolites were in the range from 0.9 ng/mL for JWH-073 to 3.0 ng/mL for JWH-200 employing liquid-liquid extraction. The developed method was applied on the separation and identification of studied analytes after liquid-liquid extraction of spiked urine and serum samples to demonstrate the potential of the method applicability for forensic and toxicological purposes.
Keywords: Synthetic cannabinoid; Liquid-Liquid Extraction; Cannabinoids; Tandem Mass Spectrometry; Micelles; Micellar electrokinetic chromatography; lidé; Heptanoic Acids; Chromatography, Liquid; kanabinoidy; Biological fluid; Chromatography, Micellar Electrokinetic Capillary; chromatografie micelární elektrokinetická kapilární; Fluorocarbons; limita detekce; tandemová hmotnostní spektrometrie; kyseliny heptylové; Tandem mass spectrometry; micely; extrakce kapalina-kapalina; Limit of Detection; fluorokarbony; Metabolites; Perfluoroheptanoic acid; chromatografie kapalinová; Humans